Longman dictionary of contemporary English. - Mayor, Michael, ....- (Harlow, Essex : Pearson Education, 2009)
Now with the unique Longman Vocabulary Trainer Fully updated for 2009, and with a brand-new, user-friendly design, this edition is full of exciting new features to help learners become fluent in English, including cutting-edge software to build vocabulary faster. The Longman Dictionary of Contemporary English provides the ultimate active learning tool - and is now available in a format to suit everyone. Whether in print, on DVD-ROM, online or via a PDA or mobile phone, you can access the best language support whenever and wherever you want - simply no other learners' dictionary compares.
Keywords: Engels -- Woordenboeken